2017
DOI: 10.1371/journal.pone.0188907
|View full text |Cite
|
Sign up to set email alerts
|

Low empathy-like behaviour in male mice associates with impaired sociability, emotional memory, physiological stress reactivity and variations in neurobiological regulations

Abstract: Deficits in empathy have been proposed to constitute a hallmark of several psychiatric disturbances like conduct disorder, antisocial and narcissistic personality disorders. Limited sensitivity to punishment, shallow or deficient affect and reduced physiological reactivity to environmental stressors have been often reported to co-occur with limited empathy and contribute to the onset of antisocial phenotypes. Empathy in its simplest form (i.e. emotional contagion) is addressed in preclinical models through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 113 publications
(136 reference statements)
7
49
0
Order By: Relevance
“…Witnessing the pain of another was sufficient to increase the individual response to the same experience. Relevantly, modulation of pain sensitivity, later confirmed by other studies, was found to be regulated by the degree of relatedness between the interacting individuals …”
Section: Emotion Recognition In Nonhuman Animalssupporting
confidence: 72%
See 2 more Smart Citations
“…Witnessing the pain of another was sufficient to increase the individual response to the same experience. Relevantly, modulation of pain sensitivity, later confirmed by other studies, was found to be regulated by the degree of relatedness between the interacting individuals …”
Section: Emotion Recognition In Nonhuman Animalssupporting
confidence: 72%
“…Despite the diversity in the modalities to express and/or perceive emotions, humans and other animals seem to share many homologies in their responses to other's emotions. Some of these responses, such as emotion contagion, can be similarly observed in all the species we described, from humans to mice . Similarly, the ability to perceive and use salient information from conspecifics emotional states is shared from primates to rodents .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It has been well known that different inbred mouse strains show different emotional responses to social stress, and such differences have been attributed to genetic differences of the strains . We previously surveyed multiple inbred mouse strains and found that the vicarious freezing response was highly variable among different strains.…”
Section: Main Bodymentioning
confidence: 98%
“…It has been well known that different inbred mouse strains show different emotional responses to social stress, and such differences have been attributed to genetic differences of the strains. 67,68 We previously surveyed multiple inbred mouse strains and found that the vicarious freezing response was highly variable among different strains. Importantly, the variability in observational fear was not significantly associated with the strain-specific differences in other behaviors such as conditioned fear, locomotor activity, anxiety, or 3-chamber sociability, suggesting that observational fear-specific genetic variations exist in inbred strains of mice.…”
Section: Neurexins (Nrxn1 and Nrxn3)mentioning
confidence: 99%